Gerakan Literasi Finansial di SMA Kabupaten Kubu Raya Kalimantan Barat - Heni Kuswanti; Maria Ulfah (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this study was to determine how the financial literacy movement with indicators of class basis, school cultural basis and community basis in Senior High School Kubu Raya Regency, West Kalimantan. The method used was a descriptive method with a survey form. The research subject was an economic teacher, data collection was done by interview and a questionnaire using google form. The data analysis step used the Interactive Analysis Model from Miles and Huberman. The technique of checking the validity of the data used source triangulation, technique triangulation, and participant extension. The results showed that there was no financial literacy movement in Senior High School Kubu Raya, West Kalimantan. In the school-based indicator there has never been any financial literacy training and there has been no application of the value of financial literacy in learning. On the school cultural basis indicator, there were no variations in books and financial literacy props, the frequency of borrowing financial literacy reading materials is limited to borrowing economic textbooks in the library, there were no financial literacy activities and policies, the presentation of financial literacy information was only on economic subjects, there were no sites related to financial literacy, there were no school bank while only a small number of school cooperations are active. In the community-based indicator, there were no supporting tools and media for financial literacy and there was no involvement of parents and the community in developing financial literacy.